2014
DOI: 10.1016/j.sjbs.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth, hormones levels and essential oil content of Ammi visnaga L. plants treated with some bioregulators

Abstract: The effects of foliar application of different concentrations of amino acids (tyrosine and phenylalanine) and phenolic acids (trans-cinnamic acid, benzoic acid and salicylic acid) on growth, pigment content, hormones levels and essential oil content of Ammi visnaga L were carried out during two successive seasons. It is clear that foliar application of either amino acids or phenolics significantly promoted the growth parameters in terms of shoot height, fresh and dry biomass, number of branches and number of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 24 publications
2
21
0
3
Order By: Relevance
“…These results are in harmony with those obtained by Moursy et al (1988) on Datura stramonium, Refaat and Naguib (1998) on peppermint (Mentha piperita), Habba (2003) on Datura innoxia, Balbaa and Talaat (2007) on rosemary plants and Talaat et al (2013) on ammi visnaga. Also, the results corroborate with the findings of Gamal et al (1997) on Cymbopgon citrates herb who reported Phe caused an enhancement in plant growth during vegetative and flowering stages.…”
Section: Resultssupporting
confidence: 90%
“…These results are in harmony with those obtained by Moursy et al (1988) on Datura stramonium, Refaat and Naguib (1998) on peppermint (Mentha piperita), Habba (2003) on Datura innoxia, Balbaa and Talaat (2007) on rosemary plants and Talaat et al (2013) on ammi visnaga. Also, the results corroborate with the findings of Gamal et al (1997) on Cymbopgon citrates herb who reported Phe caused an enhancement in plant growth during vegetative and flowering stages.…”
Section: Resultssupporting
confidence: 90%
“…L'HE de l'A. visnaga de Giza en Egypte tout comme celle de Constantine en Algérie ont été identifiées comme contenant de l'acide 2,2-diméthylbutyrique à 28.9% et 30.1% ainsi que du thymol à 13.2% et 6% respectivement [18,23]. En Turquie cette HE est plutôt dominée par le nérol (29.98%) et le bisabolol (20.86%) [34].…”
Section: Souches Bactériennesunclassified
“…Elle est douée d'activité antispasmodique et est pré-conisée lors de crampes d'estomac, de calculs rénaux, de coliques néphrétiques et de douleurs au niveau du tractus urinaire [3][4][5]7,8]. Elle sert également de remède contre l'asthme, l'angine de poitrine, les maladies cardiovasculaire, le diabète et le vitiligo [3,[9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The results suggest that the application of citric acid in higher concentration promotes the accumulation of dry matter in the sprouts, possibly through the participation in the synthesis of growth hormones that control and coordinate cell division (Amin et al, 2016). Similarly, AB at concentrations of 5-20 mg L -1 stimulates growth and elevates levels of growth promoters in Ammi visnaga L. (Talaat et al, 2014). In addition, the AB increases the dry matter content and yield in soybean plants at concentrations of 100 to 400 mg L -1 (Anjum et al, 2013).…”
Section: Resultsmentioning
confidence: 99%